2011
DOI: 10.5152/tjh.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and histopathological effects of topical Ankaferd hemostat on major arterial vessel injury related to elevated intra-arterial blood pressure

Abstract: Objective: The aim of this study was to assess the surgical and histopathological hemostatic effects of topical Ankaferd blood stopper (ABS) on major arterial vessel injury related to elevated intra-arterial blood pressure in an experimental rabbit model. Materials and Methods: The study included 14 New Zealand rabbits. ABS was used to treat femoral artery puncture on 1 side in each animal and the other untreated side served as the control. Likewise, for abdominal aortic puncture, only 50% of the aortic injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(19 reference statements)
0
9
0
1
Order By: Relevance
“…The pleiotropic effects of ABS were ascribed to the ABS-induced alterations in the pathobiological events of apoptosis [7][8][9] , angiogenesis 13,21,22 , cellular proliferation 23,24 , and cellular dynamics. 13,21 In the previous investigations, histopathological examination of the damaged vascular structures revealed ABS-induced red blood cell aggregates 1,6,25 supporting the hypothesis that ABS-induced formation of the protein network with vital erythroid aggregation covers the entire physiological hemostatic process.…”
Section: Discussionmentioning
confidence: 74%
“…The pleiotropic effects of ABS were ascribed to the ABS-induced alterations in the pathobiological events of apoptosis [7][8][9] , angiogenesis 13,21,22 , cellular proliferation 23,24 , and cellular dynamics. 13,21 In the previous investigations, histopathological examination of the damaged vascular structures revealed ABS-induced red blood cell aggregates 1,6,25 supporting the hypothesis that ABS-induced formation of the protein network with vital erythroid aggregation covers the entire physiological hemostatic process.…”
Section: Discussionmentioning
confidence: 74%
“…Those pleiotropic effects were ascribed to the ABS-induced alterations in apoptosis, angiogenesis, cellular proliferation, and cellular dynamics [46]. In previous investigations, histopathological examination of the damaged vascular structures revealed ABS-induced red blood cell aggregates supporting the hypothesis that ABS-induced formation of the protein network with vital erythroid aggregation covers the entire physiological hemostatic process [42, 43]. We have observed the same structures in the kidney tissue in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Biochemical tests also revealed that total protein, albumin, and globulin levels significantly decreased with the interactions of ABS. Red blood cells form vital erythrocyte mass blocks in the presence of ABS [Ulus 2011]. The basic mechanism of action for ABS appears to be the formation of an encapsulated protein network for erythrocyte aggregation.…”
Section: Discussionmentioning
confidence: 99%